PARALLEL SOCIETIES OF INTERNATIONAL STUDENTS IN AUSTRALIA connections, disconnections, and a... global pandemic. - Gomes, Catherine ([S.l.] : ROUTLEDGE, 2021)
"Parallel Societies of International Students in Australia explores the social and cultural spaces that international students occupy in destination countries. It specifically examines the connections they make and the significance of this parallel society in helping them become resilient, empowered and self-sufficient. It further explores the way in which international students become disconnected from the family and friends they left behind at home, as well as from local communities. Drawing on a decade worth of research into the social, cultural, real and digital spaces occupied by international students in Australia, the book also reflects on the biggest challenge humanity has faced in a hundred years; the COVID-19 global pandemic. It considers the impact that the decisions made by the Australian government and international education stakeholders in response to this evolving crisis have had on international students. This book will be of interest to academics and stakeholders involved in international education and working with international students"--
Prologue -- International student parallel societies and why they matter -- Connections -- Disconnections -- Expectations, misconceptions and misunderstandings -- A crisis of pandemic proportions.
Keywords: Students, Foreign -- Australia -- Social conditions; Foreign study -- Australia; Student affairs services -- Australia; International education -- Australia; Education and state -- Australia; COVID-19 (Disease) -- Social aspects -- Australia; EDUCATION / General